ANALISIS PROFITABILITAS USAHATANI PEMBIBITAN HORTIKULTURA DI KECAMATAN BANDUNGAN KABUPATEN SEMARANG - Noki Rachmat Fadli; Titik Ekowati; Bambang Mulyanto S. (University of Jember, 2019)
The study aims to analyze the income and profitability of horticultural nursery farmers in Bandungan District, Semarang Regency. The study was conducted in March to April 2018 in Bandungan District, Semarang Regency. The research method used was a survey method. The data taken in this study were primary data and secondary data. Data were collected by direct interviews with farmers based on questionnaires. The sampling technique used snowball sampling with a sample of 30 farmers. The data obtained were then tabulated and analyzed by one sample t test. The results showed that the average income in horticultural nursery farming was IDR 61,019,233/year. The average income per respondent of horticultural plant nurseries in Bandungan District was IDR 5,084,936/month. The income of horticulture nursery farming was greater than the UMK of Semarang Regency. The average farm profitability per respondent of horticultural plant nurseries in Bandungan District was 48.81%. The average profitability of farming per plant was 64.26%. The profitability value of farming in Chili Rawit, Chili Curly, Tomato, Eggplant, Cauliflower in Bandungan District is profitable because the profit rate was greater than Bank BRI's deposit interest rate and loan interest rates.